2014
DOI: 10.1080/09593330.2013.873485
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of non-ionic surfactant with different ethoxy groups in aqueous effluents by the photo-Fenton process

Abstract: The photo-Fenton process was applied to degrade non-ionic surfactants with different numbers of ethoxy groups, seven (E7), ten (E10) and twenty-three (E23). The effects of H2O2 concentration, Fe(II) concentration and number of ethoxy groups on the mineralization of surfactants were investigated. The response surface methodology (RSM) was applied to determine optimal concentrations of Fenton's reagents for each surfactant. The efficiency of the photo-Fenton process reached 95% for all surfactants studied at 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the Prof. Chiavone-Filho and Prof. Nascimento research groups, several homogenous photo-chemical reactors [23][24][25][26] have been tested over the years, and for none of the cases, the stoichiometric excess of H2O2 was pointed out categorially. Even though dating back to the outstanding fast mineralization earliest obtained by Silva et al [23], the signals of the role played by the H2O2 excess were hidden there, but the H2O2 excess had remained unnoted by Silva et al…”
Section: Discussionmentioning
confidence: 99%
“…In the Prof. Chiavone-Filho and Prof. Nascimento research groups, several homogenous photo-chemical reactors [23][24][25][26] have been tested over the years, and for none of the cases, the stoichiometric excess of H2O2 was pointed out categorially. Even though dating back to the outstanding fast mineralization earliest obtained by Silva et al [23], the signals of the role played by the H2O2 excess were hidden there, but the H2O2 excess had remained unnoted by Silva et al…”
Section: Discussionmentioning
confidence: 99%
“…With a high production value estimated over 18 million tons [80], their wide use generates the disposal of large amounts of these compounds in WWTPs or improperly directly into the aquatic environment without any kind of treatment. Their amphoteric character allows them to be accumulated in sediments, sludge and biota, generating concern about the potential related hazard to the environment [81].…”
Section: Surfactantsmentioning
confidence: 99%
“…Not surprisingly, the oxidant concentration has been the most controversial parameter with regard to the extent of mineralization. To illustrate the problem, we recall that sometimes the hydrogen peroxide (H2O2) is suggested to be added in a continuous flow, (da Silva et al, 2014;Esteves et al, 2019a;Moraes et al, 2004;Vilar et al, 2020) that means the overall oxidant content is fragmented over time into several doses of small quantities (Esteves et al, 2019b;Mota et al, 2018) , or even suggested to be added all at once in the treatment onset (Cunha-Filho et al, 2020) . What would be the most costeffective dosing program of the precursor oxidant, namely the H2O2?…”
Section: Time-resolved Analysis Of the Radiation Dose Commensurate Wi...mentioning
confidence: 99%